Design DVD přehrávače - Blahynka, Roman (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2011)
Předmětem této bakalářské práce je návrh designu stolního DVD přehrávače. Text komplexně popisuje tvorbu návrhu – začíná analýzou vývoje stolních přehrávačů od vynalezení až po současné trendy, pokračuje rozborem technických náležitostí přehrávače a končí popisem samotného procesu navrhování variant řešení. Poslední část textu uvádí podrobný popis aspektů definitivního návrhu a jeho obrazovou dokumentaci.

This bachelor‘s thesis concerns the design of a desktop DVD player. The text comprehensively describes the design development – it starts with an analysis of the history of desktop players from their inception to contemporary trends, continues with a breakdown of the technical requirements, and ends by describing the design process itself. The last part of the text contains detailed description of all the aspects of the final design and its visual documentation.
Design of DVD/Blu-Ray player
Keywords: DVD přehrávač; Blu-ray; HDD; stolní přehrávač; multimediální přehrávač; přehrávač; design; DVD player; Blu-ray; HDD; desktop player; multimedia player; player; design